2020
DOI: 10.1177/0022219420970196
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of the Impact of Professional Development on Teachers’ Knowledge, Skill, and Self-Efficacy in Data-Based Decision-Making

Abstract: The purpose of this review was to synthesize research on the effect of professional development (PD) targeting data-based decision-making processes on teachers’ knowledge, skills, and self-efficacy related to curriculum-based measurement (CBM) and data-based decision-making (DBDM). To be eligible for this review, studies had to (a) be published in English, (b) include in-service or pre-service K–12 teachers as participants, (c) use an empirical group design, and (d) include sufficient data to calculate an effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 42 publications
(89 reference statements)
1
21
0
Order By: Relevance
“…In addition, the authors found that prior and current PD in special education for GETs was associated with improved academic outcomes even for students outside of special education. In a meta-analysis of PD centered on data-based decision-making (DBDM), Gesel et al (2021) found that PD positively impacted teacher outcomes, a finding that complements the work of others who found that DBDM positively impacts student outcomes (Didion et al, 2020;Filderman et al, 2018;P. G. Jung et al, 2018).…”
Section: Increasing Teacher Preparedness and Supportmentioning
confidence: 83%
“…In addition, the authors found that prior and current PD in special education for GETs was associated with improved academic outcomes even for students outside of special education. In a meta-analysis of PD centered on data-based decision-making (DBDM), Gesel et al (2021) found that PD positively impacted teacher outcomes, a finding that complements the work of others who found that DBDM positively impacts student outcomes (Didion et al, 2020;Filderman et al, 2018;P. G. Jung et al, 2018).…”
Section: Increasing Teacher Preparedness and Supportmentioning
confidence: 83%
“…Teachers must undergo continuous professional development (Gesel et al, 2020). Many schools do not have the time and resources to develop their teachers.…”
Section: Issue 8 -Teacher's Continuous Professional Developmentmentioning
confidence: 99%
“…Earlier we suggested that teachers need directed, guided instruction to successfully read and interpret CBM graphs and to determine how and what to adjust in their instruction (see also Gesel et al, 2020; Wagner et al, 2017). A similar argument was made by Wayman and Jimerson (2014), who emphasized the need for general education teachers to receive professional training in data use for effective DDI implementation.…”
Section: Teachers Do Not Receive Sufficient Instruction On the Data-based Decision-making Aspects Of Cbmmentioning
confidence: 99%